Intrinsinc work motivation and pension reform acceptance - Heinemann, Friedrich; Hennighausen, Tanja; Moessinger, Marc-Daniel (Mannheim, 2011)
"Reforms, such as a higher pension age, are highly unpopular although they are a demographic necessity. Hence, a sound understanding of reform resistance is desirable. Preceding studies have explored numerous important drivers of pension reform acceptance. According to these insights, an individual’s socio-economic characteristics like gender, income or age matter as does the degree of information on the extent of the system imbalances. So far, however, the literature has not looked into another potential source of reform resistance which is related to an individual’s (dis-)utility from work. Thus, this contribution argues that intrinsic motivation must not be overlooked in a comprehensive analysis of pension reform preferences. Pension reforms impose or reduce restrictions on ageing citizens to offer their work at the labor market. Therefore, an individual’s work motivation should have an impact on reform preferences. People with intrinsic work motivation will be less anxious about longer working years compared to people for whom work is a burden. To specify the theoretical link between work motivation and pension reform acceptance, we regard the formation of pension age preferences within the framework of an optimal job separation decision. In this framework, a higher pension age should be a relatively attractive reform option for intrinsically motivated workers compared to the reform alternatives of cutting pensions or increasing contributions. In the empirical part, this prediction is tested for data from the representative ALLBUS survey (German General Social Survey) of the German population. The results strongly confirm that (lacking) intrinsic work motivation is a robust determinant for individual (resistance and) support for a higher pension age. This key result has numerous implications, both for the intrinsic motivation literature and our understanding of reform processes. So far, intrinsic motivation has been recognized to be important for the efficiency of firms and organizations. Our findings point beyond that insight towards the formation of policy preferences and the adaptability of modern welfare states and societies. A lack of non-monetary incentives will contribute to the blockade of reforms which require more work effort. Hence, a society for which work is perceived as a nuisance will have much larger problems to adjust to the necessities of demographic change compared to a society with high work ethics."